PENGARUH REVITALISASI POSYANDU TERHADAP PARTISIPASI KADER DI WILAYAH KERJA PUSKESMAS NAMORAMBE KABUPATEN DELI SERDANG - Tiffani Lubis; Saiful Batubara (Kapital Deli Sumatera, 2022)
ABSTRACT The aim of this research is to analyze the influence of revitalization on Posyandu (Integrated Service Post), such as : the training, the development of service range, support, the participation of community and the partnerships with the cadres of Posyandu in the working area of the health center in Namorambe Deli Serdang District. The type of this research was explanatory survey determined to explain the causal relationship between variables through hypothesis experiment. Population and sample in this research was all of the 46 active cadres who perform the service at Posyandu in the working area of health center in Namorambe. The analysis data was collected using logistic regression test. The result of this research indicates that training variable, support, and participation of community and partnership can influence the participation of cadres. Variable for the development of service range didn't influence the participation of cadres. The most dominant risk factors that influence the participation of cadres are the training and the participation of community, and the partnerships that controlled by support variable before. Suggestions are recommended in this case : 1). Te local government, should allocate particular fund from the Local General Revenue and Expenditure Budget to fulfill the training utilities and facilities ; 2). District Health Service and Health Center in Namorambe should give training continuously and mini workshop for every three months ; 3). Healthworkers who work at health center in Namorambe should give clear directions continuously to cadres invite the community to play a role in supporting the activity of the Integrated Health Service Post.